A Simple Technique for Procuring Liver Allografts While Protecting Arterial Vessels. (September 2014) - Memeo, Riccardo; Subar, Daren; de'Angelis, Nicola; Salloum, Chady; Azoulay, Daniel
Arterial injury remains a common complication during organ procurement, with negative effects on postoperative morbidity and graft survival. We describe a simple technique that helps surgeons avoid vascular injuries during isolated liver procurement (without pancreas). This simple technique has been used in 200 liver procurements without any arterial injuries.